2019
DOI: 10.1123/japa.2018-0053
|View full text |Cite
|
Sign up to set email alerts
|

No Improvement on the Learning of Golf Putting By Older Persons With Self-Controlled Knowledge of Performance

Abstract: The aim of this study was to verify if older adults would benefit from a self-controlled schedule of knowledge of performance (KP) in the motor skill learning. The study's participants included 22 women and 18 men, with an average age of 68 years (SD = 2.95 years). These were divided into two groups: "Self", in which participants had control over when they received KP, and "Yoked", in which participants received KP in a paired manner with the Self group. The learning task was golf putting. Results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…Importantly, this assumption suggests caution in interpreting the performance level achieved in previous studies that investigated golf putting learning (e.g. Chauvel et al, 2012;Nunes et al, 2018;Oliveira, Denardi, Tani, & Corrêa, 2013), since we based some aspects of our task design on them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, this assumption suggests caution in interpreting the performance level achieved in previous studies that investigated golf putting learning (e.g. Chauvel et al, 2012;Nunes et al, 2018;Oliveira, Denardi, Tani, & Corrêa, 2013), since we based some aspects of our task design on them.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, existing research provides experimental protocol for motor learning (e.g. Chauvel et al, 2012;Nunes et al, 2018;Oliveira, Denardi, Tani, & Corrêa, 2013;Poolton, Maxwell, Masters, & Raab, 2006).…”
Section: Equipment and Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, selfcontrolled group with high frequency of modeling had cognitive representation significantly better than experimenter-controlled groups. Also, in a group of older adults learning a golf putting task, similar performance was demonstrated by selfcontrolled and yoked groups (Nunes et al, 2019). Likewise, the self-controlled group of college students had similar performance compared to the group with regulated feedback in the acquisition of backhand return in tennis table (Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 88%
“…These studies showed that groups that self-controlled the conditions during physical practice achieved better outcomes than yoked groups. However, some studies showed no benefit of giving the participants any choice (Wrisberg & Pein, 2002;Liu et al, 2014;McRae et al, 2015;Chiviacowsky & Lessa, 2017;Kim et al, 2019;Nunes et al, 2019). For instance, Wrisberg & Pein (2002) found no differences in the effectiveness of learning a badminton long serve in groups with different frequencies of model observation.…”
Section: Introductionmentioning
confidence: 99%